2022
DOI: 10.3390/nu14193952
|View full text |Cite
|
Sign up to set email alerts
|

SMOFlipid Impact on Growth and Neonatal Morbidities in Very Preterm Infants

Abstract: The soybean oil, medium-chain triglycerides, olive oil, and fish oil lipid (SMOFlipid) is increasingly being used worldwide without definite evidence of its benefits. We examined the effect of SMOFlipid on growth velocity and neonatal morbidities in very preterm infants. Very preterm infants who received soybean-based lipid emulsion between January 2015 and 2018 were compared with those who received SMOFlipids between 2019 and January 2022 in our neonatal tertiary center. Linear regression analysis was conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The reduction in the LOS with the use of SMOFlipid was confirmed in previous studies. (28,31) Our study also found that males were 1.6 times more likely to develop sepsis relative to females, but this increase in risk was not statistically significant (p value = 0.216). This agrees with a previous study that showed a higher incidence of sepsis in males than in females (1.7:1).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…The reduction in the LOS with the use of SMOFlipid was confirmed in previous studies. (28,31) Our study also found that males were 1.6 times more likely to develop sepsis relative to females, but this increase in risk was not statistically significant (p value = 0.216). This agrees with a previous study that showed a higher incidence of sepsis in males than in females (1.7:1).…”
Section: Discussionmentioning
confidence: 48%
“…This finding is consistent with previous studies that indicated that SMOFlipid has a protective effect against infection. (28)(29)(30) When analyzing the impact of SMOFlipid on hospitalization, the gamma regression analysis indicated that infants receiving TPN with SMOFlipid had a mean reduction in hospitalization by approximately 4.12 days compared to those without SMOFlipid. However, this reduction was not statistically significant (p = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…For example, intralipid, as well as SMOFlipid (soy oil, medium-chain triglyceride, olive, and fish-oil-based lipid emulsion), nutritional supplements known to be taken up by Kupffer cells in the liver, were reported to act as an inhibitor for their phagocytic activity [ 17 , 34 ]. However, the safety of both formulations raised concerns [ 35 , 36 ]. Another approach is the use of “decoy” nanoparticles that block the MPS, luring the MPS cells away from the intended nanodrug, and thus, prolonging its circulation time [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study found SMOFlipid was associated with lower bronchopulmonary dysplasia (BPD). However, it was associated with a higher frequency of late-onset sepsis (LOS) and delayed growth velocity [11]. A new study reported no alteration in BPD and mortality in premature infants receiving SMOFlipid during their hospital stay [12].…”
Section: Introductionmentioning
confidence: 99%